The history of Barrio Obrero a metamorphosis. - Japitana, Jenny (2002.)
This study, entitled the History of Barrio Obrero: A Metamorphosis is a descriptive study of the history of the barangay. It discusses Bo. Obrero as a relocation community, which grew and developed as a barangay. This study focuses on the events that led to the birth of the barangay and its development in terms of socio-politico economic aspects. The condition of Bo. Obrero in the year 2000 is also discussed. Thus, this study presents the changes that took place since the barangay's creation the year 2000.
Research Project (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: History -- Bo. Obrero